Stabilization for hybrid stochastic systems by aperiodically intermittent control. (February 2021) - Shen, Guangjun; Xiao, Ruidong; Yin, Xiuwei; Zhang, Jinhong
Abstract: In this paper, the mean-square exponential stabilization for stochastic differential equations with Markovian switching is studied. Specifically, a new set of sufficient conditions is derived to obtain the aperiodically intermittent control design which exponentially stabilizes the addressed hybrid stochastic differential equations. Further, stabilization problem by periodically intermittent control can be deduced as a special case from the developed results. As an application, we consider the Hopfield neutral network model with simulations to illustrate the effectiveness of developed aperiodically intermittent control design.